Alginate-Based Nanoencapsulation on Ultrasonic-Assisted Extraction of Parijoto Fruit (Medinilla Speciosa Blume) and Its Antioxidant Activity - Rissa Laila Vifta; Diah Nurlaila; Sahri Yanti (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
Parijoto (Medinilla speciosa Blume) has very strong antioxidant activity, but the bioavailability was low. Therefore, Parijoto should be formed into a nanoparticle. The research aimed to determine the characterization and IC₅₀ value of nanoencapsulated Parijoto. Encapsulation was done using ionic gelation with alginate: CaCl₂ ratio 0.05%:0.05% (b/v). The ultrasonication was modified by a variation in frequency and sonication time. The characterization of nanoparticles was carried out using PSA to show the particle size and polydispersity index (pdI), and UV-Vis Spectrophotometer to show the percent of transmittance. The antioxidant activity was determined using FRAP assay. The characterization of pre-sonicated nanoextract was 265 nm of particle size, 0,472 of PdI, and 98,29% of transmittance. The best condition of sonication effect is given from 45 Hz of frequency and 15 minutes in time. The lower particle size from sonicated nanoextract was 218 nm, 0,415 of PdI, 99,56% percent of transmittance, and IC50 value obtained 1.696±0,014 ppm with a very strong category.